Self-Disclosure Process in Gay/Lesbian Adolescents: Influencing Factors - Tommy Mozes La'lang; Ratriana Y. E. Kusumiati (Bisma The Journal of Counseling, 2023)
The problem currently being faced by gays and lesbians, especially teenagers, is how to position themselves in social life. The problems faced by gay and lesbian adolescents in expressing their sexual orientation to their families are an important topic in this study. Adolescents with non-heterosexual sexual orientation often face stigma and discrimination, which can negatively impact their mental health and confidence. This study aims to understand how the process of self-disclosure occurs in gay and lesbian adolescents, as well as what factors affect the process. To achieve this goal, the research uses a qualitative phenomenological approach, with the research subjects consisting of two adolescents, one gay and one lesbian who have self-disclosed to their families. Data were collected through in-depth observations and interviews to gain a rich picture of their experiences. The results showed that self-disclosure to the nuclear family provided significant emotional support for adolescents, although there was still a fear of negative reactions from parents. The implications of this study emphasize the importance of family support and the need for inclusive sexual education to create a more accepting and supportive environment for adolescents with diverse sexual identities.